Comparative Genomics of Thaumarchaeota From Deep-Sea Sponges Reveal Their Niche Adaptation - Wang, Peng; Li, Minchun; Dong, Liang; Zhang, Cheng; Xie, Wei (Frontiers in Microbiology, 2022)
Thaumarchaeota account for a large portion of microbial symbionts in deep-sea sponges and are even dominant in some cases. In this study, we investigated three new sponge-associated Thaumarchaeota from the deep West Pacific Ocean. Thaumarchaeota were found to be the most dominant phylum in this sponge by both prokaryotic 16S rRNA amplicons and metagenomic sequencing. Fifty-seven published Thaumarchaeota genomes from sponges and other habitats were included for genomic comparison. Similar to shallow sponge-associated Thaumarchaeota, those Thaumarchaeota in deep-sea sponges have extended genome sizes and lower coding density compared with their free-living lineages. Thaumarchaeota in deep-sea sponges were specifically enriched in genes related to stress adapting, symbiotic adhesion and stability, host–microbe interaction and protein transportation. The genes involved in defense mechanisms, such as the restriction-modification system, clustered regularly interspaced short palindromic repeats (CRISPR)/Cas system, and toxin-antitoxin system were commonly enriched in both shallow and deep sponge-associated Thaumarchaeota. Our study demonstrates the significant effects of both depth and symbiosis on forming genomic characteristics of Thaumarchaeota, and provides novel insights into their niche adaptation in deep-sea sponges.